2017
DOI: 10.1016/j.ijid.2017.04.004
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the PI3K-Akt-mTOR signaling pathway in T lymphocytes in patients with active tuberculosis

Abstract: The PI3K-Akt-mTOR signaling pathway in T lymphocytes and CD4CD25FoxP3T cells was inhibited, which could explain why M.tuberculosis can induce FoxP3T cell to expand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 20 publications
(25 reference statements)
0
22
0
Order By: Relevance
“…The phosphatidylinositol 3 kinase (PI3K)/Akt signaling is crucial for cell growth, proliferation, and differentiation. It has recently been demonstrated to play important roles in regulating immune responses in many cell types [ 14 16 ]; the involvement of PI3K/Akt signaling in the interaction between epithelial cells and macrophages therefore was examined. Intriguingly, the Mtb H37Rv-activated TLR signaling of U937-derived macrophage-like cells was almost completely abolished or inhibited by the addition of PI3K inhibitor LY294002 at final concentration of 100 μ M (Santa Cruz, Santa Cruz, CA, USA) as determined by an immunoblotting assay (Figures 4(a) and 4(b) ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The phosphatidylinositol 3 kinase (PI3K)/Akt signaling is crucial for cell growth, proliferation, and differentiation. It has recently been demonstrated to play important roles in regulating immune responses in many cell types [ 14 16 ]; the involvement of PI3K/Akt signaling in the interaction between epithelial cells and macrophages therefore was examined. Intriguingly, the Mtb H37Rv-activated TLR signaling of U937-derived macrophage-like cells was almost completely abolished or inhibited by the addition of PI3K inhibitor LY294002 at final concentration of 100 μ M (Santa Cruz, Santa Cruz, CA, USA) as determined by an immunoblotting assay (Figures 4(a) and 4(b) ).…”
Section: Resultsmentioning
confidence: 99%
“…This cellular signaling has been suggested to have an important implication in the pathogenesis of tuberculosis. Indeed, the PI3K/Akt/mTOR signaling pathway was impaired in the T lymphocytes of patients with active tuberculosis [ 16 ]. It has been demonstrated that BCG could activate phosphorylation of Akt in host cells.…”
Section: Discussionmentioning
confidence: 99%
“…Since mTOR signaling pathway regulates several cellular processes, including autophagy, that are linked to the host immune response to pathogens, it is an attractive target for developing/testing small molecules to modulate host immunity for better protection against infectious agents. Moreover, the peripheral blood mononuclear cells (PBMCs) and CD 4+ CD 25+ FoxP 3+ Treg cells isolated from active tuberculosis patients demonstrated mTOR inhibition during infection (Zhang et al, 2017 ). In contrast, mTOR activation, by deletion of Tsc1 in hematopoietic stem cells, induces accumulation CDK (cyclin-dependent kinase) inhibitors p16 ink4a , p19 Arf , p21 Cip1 leading to impaired hematopoietic system and decreased lymphopoiesis (Chen et al, 2009 ).…”
Section: Mtor Inhibitors As Potential Hdt For Tbmentioning
confidence: 99%
“…After negatively regulated by this pathway [19]. The FoxP3+Treg cells activation which will assist to set up a new target for the involvement of TB immunotherapy molecules as part of the immune-escape mechanism to provide a theoretical basis is inhibited by M.tuberculosis [20].…”
Section: Some Beneficial Events With Respect To Host Cell Reverted Bymentioning
confidence: 99%